PEMANFAATAN APLIKASI MIND MAP SEBAGAI MEDIA INOVATIF DALAM PEMBELAJARAN MATA KULIAH PENGEMBANGAN PENDIDIKAN KEWARGANEGARAAN SEKOLAH DASAR - Widodo, Susilo Tri; Salam, Rudi; Prasetayaningtyas, Fitria Dwi (PKn Progresif, 2016)
This study was conducted to develop an innovative medium in learning Elementary School-Civic Education (PKn SD) Development course in order to improve the lecturer competency in developing good learning media, improving learning quality, and producing a computer and internet-based media product. The development of innovative media in this study was carried out by utilizing mind map application available in internet. This study was taken place in Elementary School Teacher Education, Pedagogic Faculty, Semarang State University. The subject of research consisted of corresponding students and lecturers. This study was an educational research with research and development approach. The procedure of research included preliminary study with descriptive qualitative approach, media development design, design validation and design improvement, and followed with limited trial on media design by applying experimental method (before-after), and product revision, if any, and final product development. The result achieved in this study was that the author had conducted a preliminary study by mapping competency and indicator into PKn SD Development course and then designed the lecturing learning plan as needed by utilizing the mind map application as learning media. The author had designed an innovative media using mind map application and had the media design validated by the competent validators in their area. The mind map application-based learning media had been tried out in treatment class. The result of test with the data processed by the author showed the following result. 1) The result of pretest and posttest showed significant improvement; it could be seen from the number of correct answer minimally 5 (40%) and maximally 13 (63%) in pre-test result and minimally 16 (80%) and maximally 20 (100%) in posttest result. 2) The result of content quality and objective aspect questionnaire before and after using mind map application showed the ratio of 55%: 89%, with instructional quality aspect of 54% : 88%, and technical quality aspect of 51% : 90%, so that the overall ratio was 54% : 89%. Considering the result of data analysis, it could be found that the mind map application use can be developed further as an innovative learning media utilizing computer technology and informatics technology mastery support. The author organized the result of study into a scientific article to be published and organized a final report as accountability.